The impact of Wavelight Technology on performance and pacing and tactical behavior in 1500-m Diamond League races - Comino, P.; Walt, M.; Casado, A. (International Journal of Sports Physiology and Performance, 2026)
Purpose: To determine the impact of Wavelight Technology on performance and tactical and pacing behavior in 1500-m Diamond League events.